1995
DOI: 10.1007/bf02064386
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin is a potent protective agent against alcohol-induced gastric injury in the rat

Abstract: Cholecystokinin is a gastrointestinal hormone known to physiologically regulate pancreatic protein secretion and gallbladder contractility. Some evidence suggests that cholecystokinin is also involved in the maintenance of gastrointestinal mucosal integrity. This study was undertaken to ascertain whether cholecystokinin could prevent the gastric mucosal injury induced by acidified ethanol and what role prostaglandins, and type A and type B cholecystokinin receptors might play in this process. Conscious, fasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Similar protective actions of exogenous gastrin and CCK have also been reported in earlier studies performed in alcohol-induced gastric injury models [13][14][15]. These studies have shown that the gastroprotective action of the gastrin was mainly mediated by mucosal defense mechanisms whereas that of CCK was mainly mediated by endogenous prostaglandins.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Similar protective actions of exogenous gastrin and CCK have also been reported in earlier studies performed in alcohol-induced gastric injury models [13][14][15]. These studies have shown that the gastroprotective action of the gastrin was mainly mediated by mucosal defense mechanisms whereas that of CCK was mainly mediated by endogenous prostaglandins.…”
Section: Discussionsupporting
confidence: 65%
“…It has been already reported that bombesin prevents macroscopic gastric injury caused by 96% ethanol given orogastrically to conscious rats [33]. Bombesin maintained the integrity of the gastric epithelium by decreasing the depth of the damage caused by the irritant [14]. In the saline-treated rats, acidified ethanol caused severe necrosis of the gastric epithelium down to the submucosa.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations